The Implementation of SAK-EMKM at Randy Variasi Store in Sukamakmur Village of Marga Sakti Sebelat Sub-District in North Bengkulu - Ulfatun Hasanah; Sulisti Afriani; Wagini Wagini (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the financial statements of randy variasi store in Sukamakmur Village, Marga Sakti Sebelat Sub-District, North Bengkulu, whether it includes Financial Accounting standards for micro, small, Medium Entites (SAK EMKM). This type of research is descriptive and comparative. The data analysis technique used is a qualitive method, namely the theoretical concept and description of the object of research as well as a comparison of the two presentations of the research results by collecting financial data made by the store. The research found that the store has not compiled and presented financial reports in accordance with the provisions of the financial accounting Standards for Micro Small and Medium Entites (SAK-EMKM), the store is supposed to presents 3 (three) types of financial statements, namely statements in practive, Randy Variasi Store only provides monthly cash statements and annual cash reports.